Upaya Perbaikan Pembelajaran Mengenal Angka 1-20 Melalui Kegiatan Menghitung Daun Ketela Pohon di Taman Kanak-Kanak - Marawani , Ziliwu; St. Maria, Ulfah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
The purpose of this study was to determine how to recognize numbers 1-20 at Kasih Tulus Kindergarten. The ones to be studied are in class B with a total of 8 children. Female 4 people, male 4 people. This research was conducted in October 2022/2023 which is located at Tanjung Anom Kec. Pancur batu Deliserdang Regency. There are also types of research carried out, namely data collection, and observation and documentation through classroom action research methods. The focus in this study is to recognize and write numbers well. The results of research in Cycle I show that children's development has not reached the maximum level, with a percentage of Speaking (BB) of 25%, Mentioning (MB) 25%, and Can Connect Letters (BSH) 50%. The weaknesses of Cycle I involved a lack of teacher creativity and a lack of support from the classroom. However, through Cycle II, significant improvements were seen. The observation results in Cycle II showed an increase in children's development, with the percentage of BB reaching 12.5%, MB 0%, and BSH 87.5%. This indicates that the improvement strategy implemented provides positive results in improving learning to recognize numbers at Kasih Tulus Kindergarten.